Detectable High-Sensitivity Cardiac Troponin within the Population Reference Interval Conveys High 5-Year Cardiovascular Risk: An Observational Study. (1st July 2018) - Than, Martin P; Aldous, Sally J; Troughton, Richard W; Pemberton, Christopher J; Richards, A Mark; Frampton, Christopher M A; Florkowski, Christopher M; George, Peter M; Bailey, Samantha; Young, Joanna M; Cullen, Louise; Greenslade, Jaimi H; et al.
Abstract: BACKGROUND: Increased cardiac troponin I or T detected by high-sensitivity assays (hs-cTnI or hs-cTnT) confers an increased risk of adverse prognosis. We determined whether patients presenting with putatively normal, detectable cTn concentrations [> limit of detection and < upper reference limit (URL)] have increased risk of major adverse cardiovascular events (MACE) or all-cause mortality. METHODS: A prospective 5-year follow-up of patients recruited in the emergency department with possible acute coronary syndrome (ACS) and cTn concentrations measured with hs-cTnI (Abbott) and hs-cTnT (Roche) assays. Cox regression models were generated with adjustment for covariates in those without MACE on presentation. Hazard ratios (HRs) for hs-cTn were calculated relative to the HRs at the median concentration. RESULTS: Of 1113 patients, 836 were without presentation MACE. Of these, 138 incurred a MACE and 169 died during a median 5.8-year follow-up. HRs for MACE at the URLs were 2.3 (95% CI, 1.7–3.2) for hs-cTnI and 1.8 (95% CI, 1.3–2.4) for hs-cTnT. Corresponding HRs for mortality were 1.7 (95% CI, 1.2–2.2) for hs-cTnI and 2.3 (95 % CI, 1.7–3.1) for hs-cTnT. The HR for MACE increased with increasing hs-cTn concentration similarly for both assays, but the HR for mortality increased at approximately twice the rate for hs-cTnT than hs-cTnI. Patients with hs-cTnI ≥10 ng/L or hs-cTnT ≥16 ng/L had the same percentage of MACE at 5-year follow-up (33%) as patients with presentation MACE. CONCLUSIONS: Many patients with ACS ruled out and putatively normal but detectable hs-cTnI concentrations are at similar long-term risk as those with MACE. hs-cTnT concentrations are more strongly associated with 5-year mortality than hs-cTnI.